(untitled) (Medico Legal Update, 2020)
Background: The present study conducted for evaluation of trends in homicidal deaths with references to study the specific parameters of homicidal deaths like incidence of homicide, socio-demographic profile of victims and type of weapon used for homicide in western Mumbai region over the period of two years. Method: Study was conducted in department of forensic medicine of H. B. T. Medical College & cooper Hospital, Mumbai for period of 2 years from January 2015 to December 2016. Total 3114 of autopsies were conducted during the period of which 66 (2.11%) were of homicidal deaths. Result: Present study found homicidal deaths accounted for 2.11% of autopsies conducted in study period. Predominance of male victims (54.5%) seen over female victims (45.5%). Maximum number of victims of homicide were in the age group of 21-40 years (60.6%). Most of homicides took place at victim ‘s residence 45.45%. Arguments (45.45%) were found to be most common motive behind homicide. Hard and blunt weapon (39.4%) is commonest type of weapon used. Conclusion: The trends of homicides are varying from region to region. In most of cases the victims are well acquainted with accused and most common place of crime was victims own house all these findings indicated that homicides were as result of arguments and scuffle between them. The victims in this young age group are more aggressive and less tolerant, proper anger and stress management through the psychiatry counselling of this age group may lower homicide rate.